Sex-difference in a sport-specific performance testing tool for the start in ski cross - Gander, M.; Pfäffli, R.; Vetsch, E.; Plüss, S.; Bruhin, B. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The starting motion in ski cross (SX) can be described as an explosive upper-body movement that requires the athlete to accelerate out of the start gate by pulling on two handles. The start section is a key performance factor for SX competitions (Argüelles et al., 2011). Therefore, this study aimed to compare upper-body strength during the start movement with a sport-specific performance esting tool between gender in elite SX athletes in laboratory conditions.